Immunohistochemical Detection of NPM1 Mutation in Acute Myeloid Leukemia and its Association With Cup-like Nuclear Morphology of Blasts. Issue 4 (April 2016) - Rastogi, Pulkit; Naseem, Shano; Varma, Neelam; Varma, Subhash
Abstract : Blasts showing cup-like nuclei in acute myeloid leukemia (AML) have been identified in patients with nucleophosmin 1 gene ( NPM1 ) mutation, that is, AML with cytoplasmic NPM (NPMc+ AML). We analyzed 100 consecutive cases of AML, and defined the cutoff percentages of cup-like blasts in peripheral blood and bone marrow aspirate smears that can predict NPMc+ AML. A lower cutoff level of ≥10% blasts in peripheral blood and ≥9% in bone marrow aspirate gave an excellent specificity for NPMc+ AML and a positive-predictive value of 90.9% and a negative-predictive value of 87.6% for NPMc+ AML. Cup-like nuclei were associated with higher total leukocyte count, higher blasts percentage, AML-M1 subtype, and human leukocyte antigen-DR region negativity. Our results suggest that cup-like nuclei represent an important morphologic clue that can predict NPMc+ AML and guide toward prioritizing the further workup of AML patients.